Novel viral genomes identified from six metagenomes reveal wide distribution of archaeal viruses and high viral diversity in terrestrial hot springs. (21st December 2015) - Gudbergsdóttir, Sóley Ruth; Menzel, Peter; Krogh, Anders; Young, Mark; Peng, Xu
Summary: Limited by culture‐dependent methods the number of viruses identified from thermophilic A rchaea and B acteria is still very small. In this study we retrieved viral sequences from six hot spring metagenomes isolated worldwide, revealing a wide distribution of four archaeal viral families, A mpullaviridae, B icaudaviridae, L ipothrixviridae and R udiviridae . Importantly, we identified 10 complete or near complete viral genomes allowing, for the first time, an assessment of genome conservation and evolution of the A mpullaviridae family as well as S ulfolobus Monocaudavirus 1 (SMV1)‐related viruses. Among the novel genomes, one belongs to a putative thermophilic virus infecting the bacterium H ydrogenobaculum, for which no virus has been reported in the literature. Moreover, a high viral diversity was observed in the metagenomes, especially among the L ipothrixviridae, as indicated by the large number of unique contigs and the lack of a completely assembled genome for this family. This is further supported by the large number of novel genes in the complete and partial genomes showing no sequence similarities to public databases. CRISPR analysis revealed hundreds of novel CRISPR loci and thousands of novel CRISPR spacers from each metagenome, reinforcing the notion of high viral diversity in the thermal environment.